Surface modification of hydrogen utilisation electrodes with nanometer scale thin film by atomic layer deposition - Lee, Zi Yi (Nanyang Technological University, 2024)
In Solid Oxide Fuel Cells (SOFCs), the Oxygen Reduction Reaction (ORR) is frequently the main factor contributing to performance loss at lower operating temperatures. Improvement to the ORR kinetics involves increasing the active Triple Phase Boundary (TPB) density which can be achieved through the modification of the surface structure and employing a highly active and thermally stable catalyst. In this study, Plasma-Enhanced Atomic Layer Deposition (PEALD) is utilised for ultralow-loading of Ruthenium (Ru) catalyst on Sr2Fe1.5Mo0.5O6 (SFMO) cathode in SOFC. The result obtained indicates that employing PEALD Ru catalyst to the SFMO cathode significantly improves SOFC performance. The cell treated with five cycles of PEALD Ru demonstrated a 42.86% increase in maximum power density and roughly a 33% decrease in polarisation resistance in comparison to the bare cell. These results imply that PEALD Ru successfully improves the cathode's ORR kinetics, which results in increased power density and decreased resistance. Overall, this study opens the door for more optimisation and implementation in sustainable energy systems by highlighting the potential of PEALD Ru catalysts to improve SOFC performance.